Is the velocity perturbation method suitable for the calculation of the useful mechanical power output of sprint kayakers in outdoor conditions? - Mourao Rossi, M.; Shamsul, N. S.; Kudo, S.; Boey, D. (ISBS Proceedings Archive (Michigan), 2022)
This study assessed whether the Useful Mechanical Power Output (PMO) estimated using the Velocity Perturbation Method (VPM) would be a valid biomechanical measure of performance enhancement in sprint kayaking that would not be affected by changes in environmental conditions. Twelve national-age K1 sprint kayakers performed twelve trials each of 60m maximal effort sprints within two separate sessions, six of which were conducted while towing a hydrodynamic object of known resistance. The opposing wind condition in each trial was recorded and classified as either mild or strong. The sprint velocities at towing-free and towing conditions under similar wind velocities and the resistance of the hydrodynamic object were matched to estimate the PMO. Non-significant differences in PMO between mild and strong wind conditions were observed. However, the typical error of PMO in both wind conditions were larger than 26% of the mean values, which hindered the ability of the PMO to detect the smallest worthwhile enhancement that would be valuable for high-performance kayak sprinting.